Karakterisasi Cendawan Rizosfer Kebun Jeruk Organik dan Potensinya dalam Menghambat Pertumbuhan Botryodiplodia theobromae dan Colletotrichum gloeosporioides - Triasih, Unun; Wuryantini, Susi; Agustina, Dina (Jurnal Fitopatologi Indonesia, 2022)
Characterization of Soil Rhizospheric Fungi on Citrus Plantation and Their Potential to Inhibiting the Growth of Botryodiplodia theobromae and Colletotrichum gloeosporioides The rhizosphere soil around the roots of citrus plants has microorganisms, one of which is a fungus. The aim of this study was to identify the rhizosphere fungi of Siam Pontianak organic citrus gardens and their potential to inhibit the growth of the pathogenic fungi Botryodiplodia theobromae and Colletotrichum gloeosporioides. The characterization of the fungus was carried out by evaluating its growth at different temperatures, humidity and pH levels, then an antagonist test was performed on C. gloeosporioides and B. theobromae. The fungi obtained from the rhizosphere of Siam Pontianak citrus organic farming were Fusarium sp., Fusidium sp., Penicillium sp., Trichoderma sp. All rhizosphere fungi grow optimally at pH 4.5–5.5, temperature 20–30 ℃ and humidity 60–80%. The fungus Penicillium sp. had the highest ability to inhibit the growth of C. gloeosporioides (83.66%), while Trichoderma sp. able to inhibit the growth of the highest pathogen B. theobromae (92.04%). Further studies are needed before applying the obtained fungal isolates as biocontrol agents for C. gloeosporioides and B. theobromae.